Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes